(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Afew decades ago, there was no Pakistan. The land now called Pakistan wasearlier part of India which came into being as a result of the two-nationtheory promoted by the Muslim League leader, Mohammad All Jinnah. Conflictsbetween Muslim League and Congress, leadership of Jinnah, Muslim’s support tofavors British rulers were some of the major factors contributing towards thecreation of Pakistan.